EFFECT OF RISK EVALUATION ON PERFORMANCE OF FINANCIAL INSTITUTIONS - Lagat, Fredrick Kiprop (Journal of Accounting, 2017)
Purpose: The purpose of the study was to determine the effect of risk evaluation on performance of financial institutions. Methodology: The study used explanatory research design. The study used stratified random sampling to select respondents from target population comprising of managers of 46 commercial banks, 52 Micro Finance institutions (MFIs) and 200 SACCOs and a sample size of 239 respondents obtained. Data was collected using questionnaires. Descriptive statistics was presented, while inferential statistics was done using Pearson product moment correlation. Results: There was a positive influence of risk evaluation [r = .813, p<.05] on the performance of financial institutions was obtained. The risk evaluation positively influenced the performance of financial institutions. The risk evaluation had positive relationship with performance of financial institutions (P<0.05). The null hypothesis HO3 stating that there is no significant effect of risk evaluation on performance of financial institutions was rejected. This indicates that for each increase in the risk evaluation, there is 0.821 increase in performance of financial institutions. Unique contribution to theory, practice and policy: The study has established the importance of ownership structure as a system of corporate governance that significantly moderates the relationship between risk management practices and performance of financial institutions can exploit various risk management practices identification, analysis, evaluation and monitoring should be enhanced so as to bring efficiency in the performance of financial institutions. These may be achieved through establishment and implementation of risk identification, analysis, evaluation and monitoring policy framework which will significantly influence performance of financial institutions and enhance shareholder capabilities to evaluate all risks that can hinder the financial institutions from achieving their set objectives